Ultrasonographic and Radiographic Diagnosis of Ectopic Ureter in a Dog - de Sousa, Carmen Vládia Soares; Rocha, Caroline Coelho; Silva, Roberto Sávio Bessa da; Dutra, Araceli Alves; Rocha, Brizza Zorayd Luz Lopes; Pacó, Thays Ribeiro; Antunes, João Marcelo Azevedo de Paula (Acta Scientiae Veterinariae, 2021)
Background: Ureteral ectopia (or ectopic ureter) is a congenital anomaly of the urinary system in which the ureter inserts anywhere other than the vesical trigone. This anatomical change may have unilateral or bilateral involvement. The most evident clinical sign, occurring mostly in females, is urinary incontinence, however in some cases the condition may progress to nephritis and dilation of the renal pelvis. The diagnosis is established through imaging, and definitive treatment requires surgical approach. The present study reports a case of ureteral ectopia in a dog which was diagnosed by ultrasound and contrast radiography (excretory urography) and successfully treated by neoureterostomy. Case: A 10-month-old female American Pit Bull Terrier was attended at the Veterinary Hospital of the Federal Rural University of the Semi-Arid (UFERSA), in Mossoró, RN. Her owner reported incontinence of dark, malodorous urine since birth as the chief complaint. After clinical examination, cystitis was suspected, and a complete blood count, urinalysis, and abdominal ultrasound was requested. The blood count and creatinine were within the reference values. The presence of struvite crystals were found on urinalysis. Ultrasound examination revealed a tortuous, dilated right ureter from the renal pelvis to the urinary bladder; no uroliths were identified as a cause of potential obstruction, but the ipsilateral kidney showed increased cortical echogenicity, loss of corticomedullary definition, and moderate pelvic dilation. These findings supported a presumptive diagnosis of ectopic ureter. For the purpose of confirming this suspicion, excretory urography was performed, revealing unilateral ureteral dilation and radiopaque contrast uptake following the path of the urethra. Once the diagnosis was confirmed, surgery was performed to correct the ureteral ectopia using the standard neoureterocistostomy technique. Considering the unilateral involvement, location of the insertion, and preserved renal function, the decision was made to perform a neoureterostomy. During the surgery it was possible to identify that the ectopic ureter was found to be intramural. At 2-month follow-up, urinary incontinence had resolved and control ultrasound showed significant improvement in the inflammatory appearance of the right renal parenchyma, with no signs of dilation of the renal pelvis or ureter. Discussion: Different from what happens in male dogs, females with an ectopic ureter will often present with urinary incontinence as the main (and, often, only) symptom, usually in the first months of life. As pollakiuria suggests a wide range of diseases of the urinary tract, ultrasound was considered the first-line imaging modality of choice, indispensable for ruling out other differential diagnoses such as a severe urinary tract infection, urolithiasis, or even malignancy. Despite the literature reporting that urinary incontinence persists in 44 to 67% of cases of ureteral ectopia, even after surgery in this case there was complete recovery of the patient after two months. Accessible techniques like ultrasonography and contrast radiography (excretory urography) supplemented one another in the elucidation of this case, with both demonstrating an excellent contribution to the diagnosis of ectopic ureter as well as served as support for surgical planning, enabling effective repair and consequent recovery of the patient.